2011
DOI: 10.4103/0019-5049.90616
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of different scoring systems in outcome prediction of patients with mixed drug poisoning-induced coma

Abstract: Background:Mixed drugs poisoning (MDP) is common in the emergency departments. Because of the limited number of intensive care unit beds, recognition of risk factors to divide the patients into different survival groups is necessary. Poisoning due to ingestion of different medications may have additive or antagonistic effects on different parameters included in the scoring systems; therefore, the aim of the study was to compare applicability of the different scoring systems in outcomes prediction of patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…The mortality rate in our cohort was comparable to that on reported in other prospective observational studies (9.7%) poisoning due to a combination of drugs, [39] and lower than pesticide-related fatalities (25.31%) reported in retrospective studies. [40] However, our mortality rate was higher than that reported in 2012 by the American Association of Poison Control Centers, concluding that only 1% of fatalities were exposure-related.…”
Section: Discussionsupporting
confidence: 88%
“…The mortality rate in our cohort was comparable to that on reported in other prospective observational studies (9.7%) poisoning due to a combination of drugs, [39] and lower than pesticide-related fatalities (25.31%) reported in retrospective studies. [40] However, our mortality rate was higher than that reported in 2012 by the American Association of Poison Control Centers, concluding that only 1% of fatalities were exposure-related.…”
Section: Discussionsupporting
confidence: 88%
“…There was significant relation between patient age and length of hospital stay with the mortality. This was in accordance with Eizadi-Mood et al, (2011) who reported that increasing age was associated with fatal outcome in drug-induced coma, while Bates, (2001) concluded that, the longer a patient remains in a coma the poorer the outcome.…”
Section: Discussionsupporting
confidence: 88%
“…This result was in accordance with Kheirabadi et al, (2015), also Duncan and Thakore, (2009) who suggested that it could be safe to observe poisoned patients with decreased consciousness, even if they have a GCS of 8 or less, in the emergency department. However, Eizadi-Mood et al, (2011) found that GCS has a useful role in outcome prediction of patients with drug overdose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GCS is used for assessing consciousness in all populations. [3] It has been a gold standard against which newer scales are compared. Over the years, its shortcomings like unreliability of verbal response in an intubated patient and absence of brainstem reflexes tests have come to focus.…”
Section: Introductionmentioning
confidence: 99%